Artificial Intelligence and Human Rights - Nesrin Singil (Public and Private International Law Bulletin)
The concept of artificial intelligence was first introduced in 1955 with the official proposal letter of the Dartmouth Summer Research Project prepared in Dartmouth College. With time and developments in artificial intelligence technology, the use of this concept has gained increasing popularity. Today, the effects of artificial intelligence, particularly on human rights, are being increasingly discussed in international meetings held between many states such as United Kingdom, France etc. The development of artificial intelligence technology and its integration in our lives has brought several conspiracy theories. Some people perceive it as a threat, whereas others see it as a useful technology for humanity. Artificial intelligence contributes to significant developments in several fields such as technology, health, and education. Similarly, it may contribute to the further improvement of human rights. However, its negative effects on human rights cannot be ignored. Identifying and eliminating such negative effects will also result in the prevention of human right violations. Considering the aforementioned reasons, it is essential to consider the positive and negative effects of artificial intelligence on human rights. In this study, first, the concept of artificial intelligence is detailed. Then, types of artificial intelligence based on their developments are discussed. Next, the artificial intelligence law is examined in the context ofhuman rights and subsequently, the effects of artificial intelligence applications on human rights are detailed. Finally, the artificial intelligence applications are discussed in terms of some fundamental rights and freedoms. In this framework, the effects of artificial intelligence applications on the “right to life,” “right to a fair trial,” “right to respect private and family life,” “freedom of expression,” and “principle of equality and prohibition of discrimination” are evaluated.